2003
DOI: 10.1152/ajpendo.00259.2003
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to high-fat diet-induced obesity and altered expression of adipose-specific genes in HSL-deficient mice

Abstract: -ichi Osuga, Shun Ishibashi, and Fredric B. Kraemer. Resistance to high-fat diet-induced obesity and altered expression of adipose-specific genes in HSL-deficient mice. Am J Physiol Endocrinol Metab 285: E1182-E1195, 2003. First published September 3, 2003 10.1152/ajpendo.00259.2003.-To elucidate the role of hormone-sensitive lipase (HSL) in diet-induced obesity, HSLdeficient (HSL Ϫ/Ϫ ) and wild-type mice were fed normal chow or high-fat diets. HSL Ϫ/Ϫ mice were resistant to diet-induced obesity showing highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
147
2
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(174 citation statements)
references
References 41 publications
22
147
2
3
Order By: Relevance
“…In addition, HSL-deficient mice had decreases in mRNA expressions of adipose LPL and PPARg. 43 However, the present study failed to find increases in HSL mRNA levels, possibly because of the lack of influence of both MUFA and P/S ratio on adipose HSL expression. Contrary to HSL mRNA levels, the fourfold difference in LPL mRNA levels seems to have led to the greatest difference in epididymal adipose tissue between the HMHR and OO groups.…”
Section: Discussioncontrasting
confidence: 85%
“…In addition, HSL-deficient mice had decreases in mRNA expressions of adipose LPL and PPARg. 43 However, the present study failed to find increases in HSL mRNA levels, possibly because of the lack of influence of both MUFA and P/S ratio on adipose HSL expression. Contrary to HSL mRNA levels, the fourfold difference in LPL mRNA levels seems to have led to the greatest difference in epididymal adipose tissue between the HMHR and OO groups.…”
Section: Discussioncontrasting
confidence: 85%
“…More than a decade ago, several groups demonstrated that mice systemically lacking HSL (HKO) also exhibit reduced lipogenesis and TG synthesis (6,9) and are resistant to HFD-induced obesity (8,9,36,37). This defect in lipoanabolic processes in HKO mice was associated with a marked down-regulation of PPARγ-dependent gene expression, leading to an almost complete loss of WAT in older HKO mice (6).…”
Section: Discussionmentioning
confidence: 99%
“…However, accumulating evidence suggested that a link exists between anabolic and catabolic lipid pathways (6)(7)(8)(9)(10). For example, the transcription of genes involved in both processes is activated by the adipogenic nuclear receptor PPAR-γ (4, 11).…”
mentioning
confidence: 99%
“…Until recently, HSL was believed to be the major regulatory enzyme in TAG hydrolysis. Studies in HSL-null mice, however, demonstrated normal WAT mass [68] and retained approximately 40% of TAG lipase activity [69][70][71]. While, HSL deficiency caused an accumulation of DAG in adipose tissue, no significant increase in TAG levels in WAT was observed [69].…”
mentioning
confidence: 98%